A life-history perspective on sexual selection in a polygamous species - Gao, Ke (BMC Evol Biol, 2020)
BACKGROUND: Ever since Darwin, evolutionary biologists have studied sexual selection driving differences in appearance and behaviour between males and females. An unchallenged paradigm in such studies is that one sex (usually the male) signals its quality as a mate to the other sex (usually the female), who is choosy in accepting a partner. Here, we hypothesize that in polygamous species these roles change dynamically with the mating status of males and females, depending on direct reproductive costs and benefits of multiple matings, and on sperm competition. We test this hypothesis by assessing fitness costs and benefits of multiple matings in both males and females in a polygamous moth species, as in moths not males but females are the signalers and males are the responders. RESULTS: We found that multiple matings confer fitness costs and benefits for both sexes. Specifically, the number of matings did not affect the longevity of males or females, but only 67% of the males and 14% of the females mated successfully in all five nights. In addition, the female’s reproductive output increased with multiple matings, although when paired with a new virgin male every night, more than 3 matings decreased her reproductive output, so that the Bateman gradient for females fit a quadratic model better than a linear model. The male’s reproductive success was positively affected by the number of matings and a linear regression line best fit the data. Simulations of the effect of sperm competition showed that increasing last-male paternity increases the steepness of the male Bateman gradient and thus the male’s relative fitness gain from additional mating. Irrespective of last-male paternity value, the female Bateman gradient is steeper than the male one for up to three matings. CONCLUSION: Our results suggest that choosiness in moths may well change throughout the mating season, with males being more choosy early in the season and females being more choosy after having mated at least three times. This life-history perspective on the costs and benefits of multiple matings for both sexes sheds new light on sexual selection forces acting on sexual signals and responses.